Comparison of frequency of significant electrocardiographic abnormalities in endurance versus nonendurance athletes - Brosnan, M.; La Gerche, A.; Kalman, J.; Lo, W.; Fallon, K.; MacIsaac, A.; Prior, D. L. (The American Journal of Cardiology, 2014)
Most data assessing the accuracy of electrocardiographic (ECG) screening in identifying cardiac pathology in athletes are derived from relatively unselected cohorts of subjects involved in competitive sports. We hypothesized that the prevalence of ECG abnormalities may be greater in athletes performing the greatest combination of exercise intensity and duration, namely professional endurance athletes. A total of 1,007 male and 254 female elite adult athletes underwent cardiovascular screening inclusive of an electrocardiogram, interpreted using the 2010 European Society of Cardiology guidelines. Training-related ECG changes (group 1) were more common in endurance athletes (EAs) than nonendurance athletes (NEAs; 90.8% vs 86.0%, p = 0.04), as were multiple (=2) training-related changes (78.9% vs 53.5%, p <0.0001). Group 2 ECG changes (previously considered uncommon and training unrelated) were seen in 18.1% of subjects and were twice as prevalent in EAs compared with NEAs (29.9% vs 15.1%, p <0.0001). Right ventricular hypertrophy (4.4% EAs vs 1.5% NEAs, p <0.005) and deep right precordial T-wave inversion (14.3% EAs vs 4.7% NEAs, p <0.0001) were 3 times as common in EAs. Both group 1 and group 2 changes were similarly prevalent among elite male and female athletes and were more common in EAs regardless of gender. In conclusion, ECG abnormalities are very common in elite athletes and are more common in EAs than NEAs. Right ventricular hypertrophy and deep right precordial T-wave inversion are particularly common in EAs, possibly because of increased structural and/or electrical right ventricular remodeling in this subgroup. The predictive value of ECG screening and criteria for abnormal findings in elite EAs requires specific appraisal.